Construction of a skeletal mechanism for butanol isomers based on the decoupling methodology. (15th November 2016) - Chang, Yachao; Jia, Ming; Xiao, Junhua; Li, Yaopeng; Fan, Weiwei; Xie, Maozhao
Highlights: Skeletal mechanisms for butanol isomers are developed with decoupling methodology. Butanol with branched structure produces stable species and reduces reactivity. The reactivity of butanol isomers varies with operating conditions. The fuel-related reactions determines the ignition delay time of butanol isomers. Abstract: Butanol has been recommended as an alternative for fossil fuels in the transport sector due to its potential for reducing pollutant emissions. Butanol has four isomers, i.e., n -butanol, s -butanol, i -butanol, and t -butanol. For the purpose of investigating the effect of molecular structure on the fuel kinetics of butanol, a skeletal mechanism containing 66 species and 196 reactions was constructed for the four butanol isomers using a decoupling methodology. The mechanism was validated against the measurements in various fundamental reactors and a homogeneous charge compression ignition (HCCI) engine. The predictions agree with the measurements reasonably well for all the four butanol isomers covering wide operating conditions. The results indicate that, for the four butanol isomers, the ignition delay time is significantly affected by the fuel-related reactions, whereas the laminar flame speed is dominated by the small species kinetics. The overall reactivity of butanol isomers decreases with the increased number of fuel molecular branch due to the fact that the fuel molecule with branched structure produces more stable branched intermediate species, reducing the reactivity of fuel.